Trust and governance - Braithwaite, V. A. (Valerie A.), 1951-; Levi, Margaret (Russell Sage Foundation series on trust ;, 1998)
Trust and Governance asks several important questions: Is trust really essential to good governance, or are strong laws more important? What leads people either to trust or to distrust government, and what makes officials decide to be trustworthy? Can too much trust render the public vulnerable to government corruption, and if so what safeguards are necessary? In approaching these questions, the contributors draw upon an abundance of resources to offer different perspectives on the role of trust in government. Enriched by perspectives from political science, sociology, psychology, economics, history, and philosophy, Trust and Governance opens a new dialogue on the role of trust in the vital relationship between citizenry and government.